Assessing the quality of evidence in studies estimating prevalence of exposure to occupational risk factors - Pega, Frank (2022)
Funding Information: All authors are salaried staff members of their respective institutions. This publication was prepared with financial support to the WHO from the National Institute for Occupational Safety and Health of the Centres for Disease Control and Prevention of the United States of America (Grant 1E11OH0010676-02; Grant 6NE11OH010461-02–01; and Grant 5NE11OH010461-03–00); the German Federal Ministry of Health (BMG Germany) under the BMG-WHO Collaboration Programme 2020–2023 (WHO specified award ref. 70672); the Spanish Agency for International Cooperation (AECID) (WHO specified award ref.71208). The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript. Funding Information: We thank Dr. Paul Whaley (Lancaster University) for sharing his ideas and his editorial review. Professor Carel T.J. Hulshof and Professor Monique H. Frings-Dresen (both University of Amsterdam) have prepared and shared the body of evidence from the ongoing systematic review on the prevalence of occupational exposure to ergonomic risk factors for pilot testing. Dr. Richard Brown (WHO), Professor Vivi Schl?nssen (Aarhus University) and Stevie van der Mierden (Netherlands Cancer Institute) provided feedback on QoE-SPEO and/or an earlier version of this article. At the time of development of the manuscript, SLN was affiliated with Department of Quality Assurance, Norms and Standards, World Health Organization; however their current affiliation is Oregon Health & Science University. At the time of development of the manuscript, LAB was affiliated with Charles Perkins Centre, The University of Sydney; however their current affiliation is General Internal Medicine/Public Health/Center for Bioethics and Humanities, University of Colorado?Anschutz Medical Campus. SLN is a member of the GRADE working group. LB is Senior Editor, Research Integrity, Cochrane for which The University of Colorado receives remuneration. All other authors report no conflict of interests. Publisher Copyright: © 2022